A New Password- and Position-Based Authenticated Key Exchange. (24th February 2021) - Fan, Jia; Qiao, Lanfei; Cao, Yunfei; Liu, Shanglin; Zhang, Wenke; Tang, Lin
Abstract : Password-based authenticated key exchange is a popular method for secure authentication and key exchange. With the wide application of unmanned aerial vehicles, position information has also become an important factor in authentication. In this paper, we present a new key exchange protocol, which firstly realizes dual authentication for both password and position, and we propose two applicable scenarios for the PPAKE mechanism: one is unmanned aerial vehicle authentication, and the other one is authentication in the military base. By adding position authentication, the reliability of authentication has improved, and the difficulty of adversarial attacks also increases. Any arbitrary adversary who can listen, tamper, and send messages can only perform an online attack for password guessing at a specified position. Finally, we provide security proofs under the defined model.